Estudo do isolamento sonoro de vidros de diferentes tipos e espessuras, em vitragem simples e dupla - Scherer, Minéia Johann (2005)
This work aims to determine the acoustic isolation to aerial noise of glasses used in the civil building, as insulations or frames, of different types and thicknesses, in a simple form and composing double glasses. This quantification is done by normalized assays in the reverberation chambers of the thermo-acoustic laboratory of Federal University of Santa Maria, according to international standards ISO 140 and ISO 717 and Brazilian Norm Project 02:135.01-001. First, the different types and thicknesses of glasses had been assayed individually. After, asymmetrical compositions of double glasses had been carried out, that means, using glasses of different types or thicknesses, varying increasingly the spacing between them. Based on the results of the assays, it was verified that the behavior of glasses when used individually follows basically the mass law. In relation to the compositions of double glasses, it was verified that the acoustic isolation increases relatively fast with the thickness of the air layer between the elements, when it is small. However, from a determined spacing, the ratio of increase is smaller. This way, it was possible to evaluate what are the best performance situations of the glasses tested in relation to the acoustic isolation and tocontribute for designers, manufacturers and b uilders at the moment of project or execution of an acoustically comfortable building.